(untitled) (Scientific journal of the Fergana State University, 2025)
Innovations in the activities of the primary physical culture team of a general education school are a set of new approaches and methods aimed at meeting the demands of the times, enhancing students’ physical development, promoting a healthy lifestyle, and fostering team spirit. In this annotation, we will analyze the innovations being implemented in the activities of the primary school physical culture team.